2016
DOI: 10.3389/fpsyg.2016.01812
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Perspective-Taking in Alzheimer’s Disease: A Mini-Review

Abstract: Metacognition refers to the monitoring and regulation of cognitive processes and its impairment can lead to a lack of self-awareness of deficits, or anosognosia. In the context of different neurological and psychiatric disorders (e.g., traumatic brain injury, dementia, and schizophrenia), studies have shown that patients who present impairments in metacognitive abilities may be able to recognize such difficulties in others and in themselves when exposed to material in a third-person perspective. Considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
(67 reference statements)
0
30
0
Order By: Relevance
“…Focusing on AD, Bertrand et al ( 2016 ) dwelt on the association between metacognition and perspective-taking as a key aspect for improving quality of life in AD patients. These authors specified that “ metacognition refers to the monitoring and regulation of cognitive processes and its impairment can lead to a lack of self-awareness of deficits, or anosognosia ” (Bertrand et al, 2016 , p. 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing on AD, Bertrand et al ( 2016 ) dwelt on the association between metacognition and perspective-taking as a key aspect for improving quality of life in AD patients. These authors specified that “ metacognition refers to the monitoring and regulation of cognitive processes and its impairment can lead to a lack of self-awareness of deficits, or anosognosia ” (Bertrand et al, 2016 , p. 1).…”
mentioning
confidence: 99%
“…Bertrand et al ( 2016 ) suggested that the Default Mode Network may be useful to shed light on the role of perspective-taking in awareness of deficits in AD. They presented this relationship by referring to the Cognitive Awareness Model (CAM), which incorporates a comparator system within the central executive to detect mismatches between a personal database and experience of failures and successes (Agnew and Morris, 1998 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis review suggests that approximately 35.6 million people live with dementia in 2010, and the number would increase to 65.7 million in 2030 and 115.4 million in 2050, among which 60% were on account of AD (Prince et al, 2013 ). In addition to decreased function, memory and cognition, quality of life and so on in AD patients, AD also increases caregiver burden in family members and elevated labor loss as well as social cost (Bertrand et al, 2016 ; Svendsboe et al, 2016 ; Deb et al, 2017 ). Thus AD becomes an increasingly critical issue to human health in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it becomes difficult to predict others’ reactions and respond accordingly because of the deterioration of thinking abilities. Monitoring and managing one's own behaviors also becomes difficult, owing to the deterioration of self‐monitoring and self‐control abilities …”
Section: Introductionmentioning
confidence: 99%